THE BONITATION METHOD FOR ASSESSING THE FERTILITY OF THE CHERNOZEM - Mariana BURCEA; Nicoleta OLTENACU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The aim of the paper is to analyse the dynamics of social mutations that took place in the rural area of the Danube Delta, in Tulcea County, which is part of the interest area of the project. Statistical indicators have been determined using the functions from Excel Program, such as: average, standard deviation, coefficient of variability, annual growth rate. Population in rural are of Tulcea County had a decreasing trend during the period 2012-2018 and reached in 2018 at 53.5% of population of the county. The coefficient of correlation between emigrants and population in rural areas of the county of Tulcea indicate a very good association between the two variables and determination coefficient R2 shows that 86.32% of the variation of resident rural population can be explained by linear relationship with the number of temporary emigrants. The population employed in agriculture, as the main activities of the rural area, decreased in the period 2008-2017 by almost 26%. Although the population occupied in agriculture is 10 times higher than in tourism, the upward dynamics of the tourism sector creates the premises for economic growth.